The attitudes of the economic elite toward social redistribution: the role of self-interest and solidarity - Thomsen, Jens Peter Frølund (Politica, 2017)
Traditional class theories underestimate the ability of welfare institutions to foster support for social redistribution among the economic elite. Analyses show that the economic elite is more opposed to social redistribution than ordinary employees who have no authority in the social division of labor. However, the relationship between economic elite position and attitudes toward social redistribution is relatively weak. Nor is the economic elite instinctively opposed to the political views of the working class – or instinctively in favor of the views of the upper class. The economic elite is both aware of its own interests and supportive of underprivileged groups in society. Finally, the analyses show that personal income mediates the relationship between economic elite position and attitudes toward social redistribution. The empirical analyses are performed on a (postal) class survey fielded in 2015 (n = 1,032).